Citra Inferioritas Tenaga Kerja Wanita (TKW) Indonesia di Saluran Berita Sabq.Org Saudi Arabia - Muhamad Fahrudin Yusuf (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2020)
This article is the result of research, one of which is the lack of discourse studies, especially the representation of the news object studies in electronic newspapers. News about woman employees in Saudi Arabia was chosen because there have been many cases that occurred in Saudi Arabia. Several cases such as starting from illegal migrant workers, trafficking, prostitution, suicide, and various legal circumstances that befall Indonesian workers, how the news of women employee is written on Sabq.org newspaper, one of the leading online publications in Saudi Arabia. All cannot be separated from the media representation or depiction of an object. Representatives of woman employees will be dissected based on contextual illustration-writer-text-context reader theory by Sara Mills. The qualitative method of Critical Discourse Analysis was chosen as a means for collecting data. The technique of analyzing data used in this study is using the framework of Sara Mills's analysis related to the position of subject and object of the news. The research findings showed that Sabq.org portrays woman employees poorly, marginalizes minority groups by not showing woman employees in the news, dominant groups represent their presence, establishing ideology of dominant groups (employee) and tends to be gender-biased. Artikel ini dilatarbelakangi minimnya kajian wacana, khususnya representasi pada objek kajian berita pada surat kabar elektronik (SKE). Berita tentang Tenaga Kerja Wanita (TKW) di Arab Saudi menjadi pilihan karena alasan banyaknya kasus yang terjadi pada TKW di Arab Saudi, mulai dari TKI ilegal, kasus trafficking, prostitusi TKW, bunuh diri dan beragam kasus hukum yang menimpa buruh migran wanita Indonesia. Bagaimana wacana TKW digambarkan dalam berita Sabq. Org, salah satu koran online terkemuka di Arab Saudi tidak lepas dari representasi atau penggambaran media atas suatu objek. Representasi TKW akan dibedah dengan teori ilustrasi konteks penulis- teks-konteks pembaca dari Sara Mills. Metode kualitatif Analisis Wacana Kritis (critical discourse analysis) dipilih sebagai alat mencari data. Teknik analisis penelitian ini menggunakan kerangka analisis Sara Mills terkait posisi subjek-objek berita. Hasil dari penelitian ini adalah Sabq.Org menggambarkan TKW dengan buruk, memarjinalkan kelompok minoritas (TKW) dengan tidak menampilkan TKW dalam pemberitaan, kehadirannya diwakili oleh kelompok dominan, memapankan ideologi kelompok dominan (majikan) dan cenderung bias gender.